Achieving full realization and mitigating the challenges of the Internet of Things - Odhiambo, Marcel, 1955-; Mwashita, Weston (Advances in wireless technologies and telecommunication (AWTT) book series., 2022)
"IoT technologies are being used in the re-engineering of a variety of products resulting in better performance, reduced cost, and an improved customer experience, and this book offers a variety of chapters that specifically addresses the challenges faced in the rolling out of IoT technologies "--